ANALYSIS OF EXTERNAL ENVIRONMENTAL FACTORS AT THE FOOD INDUSTRY ENTERPRISES OF THE REPUBLIC OF ARMENIA - Sergey G. Sargsyan (Статистика и экономика, 2016)
The main components of the external environment, which have a key influence on the economic activities of organizations in the food industry, are discussed in the article. The influence of certain external environment factors is examined by the example of the Republic of Armenia with taking into account the characteristics of the industry. The rates of development, the leading market indicators are analysed, as well as the key components that form the socio-economic system of the industry are considered.